Pengembangan Media Pembelajaran Kartu Suku Kata untuk Mengatasi Kesulitan Membaca Siswa Kelas 2 di MIS Ar-rahman - Shima Mutmainnah; Mardianto Mardianto; Ramadan Lubis (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The use of instructional media is expected to address learning challenges, particularly early reading difficulties among students. This study aims to develop a syllable card learning media that is valid, practical, and effective. The method used is Research and Development (R&D) with the ADDIE model, involving 29 second-grade students at MIS Ar Rahman. The research results indicate that syllable cards help students overcome reading difficulties. Validity tests by media and content experts yielded an average score of 86% (highly valid). Practicality was assessed through a teacher response questionnaire, scoring 96% (highly practical). Effectiveness was tested using a Pretest-Posttest approach, resulting in an N-Gain Score of 76% (effective category), with the students’ average pretest score at 57.9 and posttest score improving to 90.1.